STRATEGIES TO PENETRATE AGROCHEMICALS MARKET IN VIETNAM: A CASE STUDY OF FUMIGANTS - Buadit, Sunudda; Anurit, Pacapol Jakrapan; Bunchapattanasakda, Chanchai (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2016)
This article presents key strategies to penetrate the agrochemicals market in Vietnam of agochemicals entrepreneurs who run some agrochemical business owing to its increasing market potential with special reference to fumigants. The study investigated the factors reviewed from the literature that were asserted to be important to the entry to the fumigant market in Vietnam which are: entrepreneurs’ experiences in doing a business abroad, market expansion of the indus- try, internationalization, country risk, cultural difference, market potential, market knowledge, and motivation to partner with some global alliance. In order to discover key success factors that are important to strategies to penetrate the agrochemical market for fumigants and learn about the strategies used by successful entrepre-neurs of fumigants in Vietnam, non-probability sampling procedure is adapted by the judgment sample which the researchers actively select the most productive sample to answer the research questions. The participants were Thai investors who registered with Board of Investment (BOI) and Thailand Overseas Investment Center (TOI) and thus 10 of the investors who specified themselves in the agrochemical industry from each database were drawn from the database be-tween August 2014 to September 2015. With the purposive, convenience and snowball tech-nique, the research achieved data collection from 10 key informants who were Thai exporters of fumigants to Vietnam. It was ensured that all the selected interviewees were knowledgeable, highly experienced. As a result, the selected techniques were considered to be useful and suitable for empirical study. The selected key informants provided insightful perspectives on the identified factors which helps formulate key penetration strategies to the fumigant business in the agrochemical market in Vietnam. A comprehensive range of findings covers different marketing, managerial and operational factors from: value-based pricing, customer relationship management, direct marketing, flexible company’s infrastructure to adjust to the emerging market demand and con-stant changing rules and regulations especially on an incomplete public sector, readiness to deal business with new generation of Vietnamese entrepreneurs, ability to understand and deal with complexity of local entrepreneurial cultures, relationship management with the local distributors at different stages, and ability to develop businesses using co-opetition (cooperation and compe-tition) strategies with competitors and clients. กลยุทธ์การเจาะตลาดสินค้าเคมีทางการเกษตรในประเทศเวียดนาม:กรณีศึกษาสารรมควัน บทความนี้นำเสนอกลยุทธ์ที่สำคัญในการเจาะตลาดสินค้าเคมีทางการเกษตรในประชาคมเศรษฐกิจอาเซียนของผู้ประกอบการธุรกิจสินค้าเคมีทางการเกษตรซึ่งกำลังดำเนินธุรกิจเกี่ยวกับสารเคมีทางการเกษตรประเทศที่ใช้ในการศึกษาคือเวียดนามเนื่องจากเป็นประเทศที่มีศักยภาพทางการตลาดสูงขึ้นเรื่อยๆโดยเฉพาะอย่างยิ่งสำหรับสินค้าสารรมควันการศึกษานี้มีเป้าหมายหลักเพื่อค้นหาปัจจัยหลักที่ค้นพบจากวรรณกรรมว่ามีความสำคัญต่อการเจาะตลาดสารรมควันในเวียดนามได้แก่ประสบการณ์ในการดำเนินธุรกิจธุรกิจในต่างประเทศของผู้ประกอบการ การขยายตลาดของอุตสาหกรรม ความสามารถในการเข้าสู่ความเป็นสากล ความสามารถในการบริหารความเสี่ยงภายในประเทศที่เข้าไปลงทนุ การเข้าใจถึงความแตกต่างทางวัฒนธรรม การวิเคราะห์แนวโน้มหรือศักยภาพของตลาด ความร้เูกี่ยวกับตลาดที่เข้าไปลงทุน และแรงผลักดันในการร่วมมือกับพันธมิตรระดับโลกในการที่จะค้นพบกุญแจแห่งความสำเร็จที่มีความสำคัญต่อการสร้างกลยุทธ์ในการเจาะตลาดสินค้าเคมีทางการเกษตรและเรียนรู้เกี่ยวกับกลยุทธ์ที่ผู้ประกอบการที่ประสบความสำเร็จใช้อยู่ในเวียดนาม การวิจัยครั้งนี้ใช้กลุ่มตัวอย่างโดยไม่ใช้ความน่าจะเป็นโดยผู้วิจัยเลือกกลุ่มตัวอย่างโดยพิจารณาจากการตัดสินใจของผู้วิจัยเองว่ามีคุณสมบัติในการตอบคำถามได้เหมาะสมที่สุดเป็นการเลือกกลุ่มตัวอย่างแบบเจาะจงมี่อาศัยความรอบรู้ความชำนาญและประสบการณ์ในเรื่องนั้นๆโดยผู้ถูกสัมภาษ์คือนักลงทุนไทยที่ขึ้นทะเบียนกับคณะกรรมการส่งเสริมการลงทุนและศุนย์ข้อมูลการลงทุนไทยในต่างประเทศและนักลงทุนจำนวนสิบคนที่ระบุว่าลงทุนในอุตสาหกรรมเคมีทางการเกษตรในฐานข้อมูลในช่วงระหว่างเดือนสิงหาคมพ.ศ. 2557 ถึงกันยายนพ.ศ. 2558จากการใช้เทคนิคการส่มุ ตัวอย่างแบบเจาะจงแบบสะดวกสบายและแบบลูกโซ่งานวิจัยนี้สามารถเก็บข้อมูลจากผู้ให้ข้อมูลคนสำคัญจำนวน 10 คนซึ่งเป็นผู้ส่งออกสารรมควันจากประเทศไทยไปยังประเทศเวียดนาม ส่งผลให้งานวิจัยนี้ได้ข้อมูลเชิงคุณภาพที่มีคุณค่าเพราะผู้ให้สัมภาษณ์เหล่านี้เป็นผู้รอบรู้และมีประสบการณ์สูงสามารถถ่ายทอดข้อมูลเชิงประจักษ์ได้ผู้ให้ข้อมูลคนสำคัญกลุ่มนี้ได้เสนอมุมมองที่ชัดแจ้งที่ช่วยจำแนกปัจจัยที่เอื้อต่อการสร้างกลยุทธ์สำหรับธุรกิจสารรมควันในการเจาะตลาดสินค้าเคมีทางการเกษตรในเวียดนามผลการวิจัยเผยถึงการทำการตลาดที่หลากหลายและปัจจัยด้านการจัดการและการปฏิบัติการอาทิการตั้งราคาจากคุณค่าการบริหารความสัมพันธ์ลูกค้าการตลาดทางตรงความยืดหยุ่นของโครงสร้างบริษัทในการปรับตัวเพื่อรองรับอุปสงค์จากตลาดที่กำลังเกิดใหม่ซึ่งมีกฎระเบียบที่กำลังถูกเปลี่ยนแปลงโดยเฉพาะในภาคเอกชนที่ยังไม่สมบูรณ์ความพร้อมในการดำเนินธุรกิจกับผู้ประกอบการชาวเวียดนามรุ่นใหม่ความสามารถในการเข้าใจและรับมือกับความซับซ้อนของวัฒนธรรมผู้ประกอบการท้องถิ่นการจัดการความสัมพันธ์กับผู้จัดจำหน่ายในระยะต่างๆและความสามารถในการพัฒนาธุรกิจโดยใช้กลยุทธ์ผสมผสานระหว่างการร่วมมือและการแข่งขันกับคู่แข่งและลูกค้า